2013
DOI: 10.20659/jfp.18.2_141
|View full text |Cite
|
Sign up to set email alerts
|

Forests and Human Development: An Analysis of the Socio-Economic Factors Affecting Global Forest Area Changes(<Special Issue>FORCOM 2011)

Abstract: Aii Analysis of the Socio-Economic Affecting Global Forest Area Changes 'Ibtsuya Michinaka 'iandMotoe Miyamoto '2 msSIRAcr This study examined the impacts ot socio-economic factors on forest area change by human development 1ffvel of countries. Cluster analysis and panel data analysis were combined to solve the problem of heterogeneity in panel data analysis and the problem ef data availability to some extent, The results show that many soci}economic factors have negative impacts on forest area in counhies at … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Population is a factor that is considered in most socio-economic analysises (Michinaka & Miyamoto, 2013). We use the total population, which represents the size or magnitude of the population.…”
mentioning
confidence: 99%
“…Population is a factor that is considered in most socio-economic analysises (Michinaka & Miyamoto, 2013). We use the total population, which represents the size or magnitude of the population.…”
mentioning
confidence: 99%
“…Deforestation is mainly the result of human behavior due to specific socioeconomic circumstances. The roles that people play regarding forests in a country may vary when their socioeconomic circumstances change [20]. Many researchers use per capita GDP or income to reflect socioeconomic development; however, demographers have also found a population growth transition during the process of socioeconomic development in many countries and regions and have proposed a population transition theory [59,60].…”
Section: Discussionmentioning
confidence: 99%
“…Panel data analysis, an econometrics approach, was adopted in the research. Panel data analysis has been widely used in analyzing deforestation issues (e.g., [20,30,31,47]). For developing countries, long time-series data are usually not available.…”
Section: Methodsmentioning
confidence: 99%
“…Herold et al [20] and Gutman and Aguilar-Amuchastegui [21] identified three types of approaches to the establishment of a REDD+ reference level: the strictly historical approach, adjusted historical approach, and simulation models. Although forest transition theory proposes a simple model showing the pattern of forest cover changes over time, many other drivers have also been analyzed, including distance to roads and markets [22], fallow and cropping lengths [23], cultivated area [24], wood scarcity [25], land rent [7], historical deforestation, forest cover, per capita GDP, agricultural GDP, human population, road network [20], human development [26], and rural and urban populations [27], to name a few. Analysis methods have included simple regression, multiple regression, and non-linear regression at household, sub-national or national levels.…”
Section: Introductionmentioning
confidence: 99%
“…However, here we argue that, due to its availability, FAO data is still a valid choice. Michinaka and Miyamoto [26] used FAO and UNDP data in cluster and panel data analyses to evaluate forest area changes in relating to life expectancy at birth, adult literacy rate, per capita GDP, total human population, rural population rate, and agriculture GDP in 205 countries. These authors found several factors that negatively impact forest area in countries with low human development levels, but these impacts become positive in countries with higher human development levels.…”
Section: Introductionmentioning
confidence: 99%